ANALISIS FAKTOR YANG MEMENGARUHI KETIMPANGAN PENDIDIKAN - Ni'matush Sholikhah; Bambang Suratman; Yoyok Soesatyo; Ady Soejoto (Universitas Negeri Malang, 2015)
Abstract: Analysis of Factors Affecting Educational Inequality. This article presents the results of research on educational inequality in the province of East Java. This descriptive correlational study was based on the panel data obtained from the Directorate General of Budget and Fiscal Balance and the Statistics of Indonesia in the period of 2008-2012. The data were analyzed using an application program referred to as Eviews 6, with the Gini index as a measure of the degree of inequality. The analysis reveals the existence of inequality of education in the province of East Java. In addition, there is a relationship between the variables of government expenditure on education, gender gap, and the household expenditure on education and the variable of educational inequality. Keywords: educational inequality, government expenditure on education, gender gap, education of household expenditure Abstrak: Analisis Faktor Yang Memengaruhi Ketimpangan Pendidikan. Artikel hasil penelitian ini memaparkan mengenai ketimpangan pendidikan di Provinsi Jawa Timur. Penelitian menggunakan rancangan deskriptif korelasional berdasarkan data panel periode 2008-2012 yang diperoleh dari Direktorat Jenderal Perimbangan Keuangan dan Badan Pusat Statistik Provinsi Jawa Timur. Data dianalisis dengan mempergunakan program aplikasi Eviews 6, dengan indeks Gini sebagai ukuran tingkat ketimpangan. Hasil penelitian mengungkap adanya ketimpangan pendidikan di Provinsi Jawa Timur. Selain itu, terdapat hubungan antara variabel pengeluaran pemerintah bidang pendidikan, gender gap, dan pengeluaran pendidikan dari rumah tangga, dengan variabel ketimpangan pendidikan. Kata kunci: ketimpangan pendidikan, pengeluaran pemerintah bidang pendidikan, gender gap, pengeluaran pendidikan rumah tangga